Influence of hepatitis C virus co-infection and hepatitis C virus treatment on risk of chronic kidney disease in HIV-positive persons - Mocroft, Amanda; Ryom, Lene; Oprea, Cristiana; Li, Qiuju; Rauch, Andri; Boesecke, Christoph; Uzdaviniene, Vilma; Sedlacek, Dalibor; Llibre, Josep M; Lacombe, Karine; Nielsen, Lars N; Florence, Eric; et al. (AIDS (London, England), 2020)
BACKGROUND: Hepatitis C virus (HCV) infection has been associated with increased risk of chronic kidney disease (CKD). We investigated the impact of HCV cure on CKD in HIV-positive persons in the EuroSIDA study. METHODS: HIV-positive persons with known HCV status and at least three serum creatinine measurements after 1/1/2004 were compared based on time-updated HCV-RNA and HCV treatment: anti-HCV-negative, spontaneously cleared HCV, chronic untreated HCV, successfully treated HCV, and HCV-RNA positive after HCV treatment. Poisson regression compared incidence rates of CKD [confirmed (>3 months apart) eGFR <60 ml/min per 1.73 m] between HCV strata. RESULTS: Fourteen thousand, seven hundred and fifty-four persons were included; at baseline 9273 (62.9%) were HCV-Ab negative, 696 (4.7%) spontaneous clearers, 3021 (20.5%) chronically infected, 922 (6.2%) successfully treated and 842 (5.7%) HCV-RNA positive after treatment. During 115 335 person-years of follow-up (PYFU), 1128 (7.6%) developed CKD; crude incidence 9.8/1000 PYFU (95% CI 9.2-10.4). After adjustment, persons anti-HCV negative [adjusted incidence rate ratio (aIRR) 0.59; 95% CI 0.46-0.75] and spontaneous clearers (aIRR 0.67; 95% CI 0.47-0.97) had significantly lower rates of CKD compared with those cured whereas persons chronically infected (aIRR 0.85; 95% CI 0.65-1.12) and HCV-RNA positive after treatment (aIRR 0.71; 95% CI 0.49-1.04) had similar rates. Analysis in those without F3/F4 liver fibrosis using a more rigorous definition of CKD showed similar results. CONCLUSION: This large study found no evidence that successful HCV treatment reduced CKD incidence. Confounding by indication, where those with highest risk of CKD were prioritized for HCV treatment in the DAA era, may contribute to these findings.
Keywords: HIV Infections; chronická hepatitida C; koinfekce; HIV infekce; Antiviral Agents; Coinfection; Renal Insufficiency, Chronic; lidé; Hepacivirus; prospektivní studie; Prospective Studies; antivirové látky; Hepatitis C, Chronic; chronická renální insuficience; Humans